The Impact of Cognitive Behavioural Therapy on Dental Anxiety in Children: A Clinical Trial - Malani, Poonam; Tiwari, Shilpi; Kulkarni, Parimala; Gopakumar Menon, Anaghaa; Mishra, Prerna Sudhir (Journal of Neonatal Surgery, 2025)
Background: Dental anxiety is a common phenomenon experienced by children in the dental setting. Cognitive behavioral therapy (CBT) is a type of psychotherapeutic treatment that helps people learn how to identify and change the destructive or disturbing thought patterns that have a negative influence on their behavior and emotions. Though research has been done on CBT to allay dental anxiety but still its clinical applicability is less explored in dentistry. Aim: To assess and evaluate the impact of a cognitive-behavioral intervention on dental anxiety in children. Materials and methods: A total of thirty children, aged 7-10 years were included. The pre assessment anxiety and cooperation levels of the children were determined by using the Modified Child Dental Anxiety Scale (MCDAS), Venham child cooperation scale (VCCS), and Deepak-Parimala Children Perception. The intervention group (group 1) (N=15) received twenty-minute session of cognitive behavioral therapy while control group (group 2) didn’t receive any CBT intervention. After CBT in group 1, Local anesthesia was administered in both the groups. Then, the respective measuring scales were again applied. Results: There was a statistically significant difference in anxiety and cooperation levels measured by MCDAS scale, VCCS scale and Deepak-Parimala anxiety scale in intervention group as compared to control group. Conclusion: Findings of our study suggests that CBT is an effective intervention for managing dental anxiety in paediatric patients during dental procedures.